2003
DOI: 10.1046/j.1440-0952.2003.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Geology of southeast Bohol, central Philippines: Accretion and sedimentation in a marginal basin

Abstract: Recent field mapping has refined our understanding of the stratigraphy and geology of southeastern Bohol, which is composed of a Cretaceous basement complex subdivided into three distinct formations. The basal unit, a metamorphic complex named the Alicia Schist, is overthrust by the Cansiwang mélange, which is, in turn, structurally overlain by the Southeast Bohol Ophiolite Complex. The entire basement complex is overlain unconformably by a ~ 2000 m thick sequence of Lower Miocene to Pleistocene carbonate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Crustal shortening and thickening within Mindanao [Pubellier et al, 1991Sajona et al, 1994Sajona et al, , 2000 and across smaller islands of the Philippines have elevated these regions [e.g., Faustino et al, 2003;Travaglio et al, 1978]. Palawan, however, seems to have emerged by middle Miocene time (between~15 and 10 Ma) [e.g., Holloway, 1982;Rangin and Silver, 1991].…”
Section: Growth Of the Maritime Continentmentioning
confidence: 99%
“…Crustal shortening and thickening within Mindanao [Pubellier et al, 1991Sajona et al, 1994Sajona et al, , 2000 and across smaller islands of the Philippines have elevated these regions [e.g., Faustino et al, 2003;Travaglio et al, 1978]. Palawan, however, seems to have emerged by middle Miocene time (between~15 and 10 Ma) [e.g., Holloway, 1982;Rangin and Silver, 1991].…”
Section: Growth Of the Maritime Continentmentioning
confidence: 99%
“…reported that pillow basalts from the basement of Cebu record strong subductionrelated signatures. Farther east, the Southeastern Bohol Ophiolite Complex is overlain by cherts containing Early Cretaceous radiolarian and foraminiferal assemblages (Faustino et al, 2003). This ophiolite complex also displays geochemical patterns similar to those observed in SSZ-related oceanic basins (Yumul et al, 2001).…”
Section: Possible Extent Of the Proto-philippine Sea Plate In Centralmentioning
confidence: 86%
“…Previous works on Central Philippine ophiolites and ophiolitic sequences show these discrete crust-mantle slices to be of supra-subduction affinity [e.g., Tacloban, Samar, Malitbog, Southeast Bohol, Cebu] (e.g., Barretto et al 2000;Faustino et al 2003;Tamayo et al 2004;Suerte et al 2005;. Apart from the Oligocene Amnay Ophiolite in Mindoro which has the ocean island basalts (OIB) or enriched mid-oceanic ridge basalts (EMORB) component in addition to its transitional island arc tholeiite -N-MORB geochemistry (Jumawan et al 1998;Perez et al 2013), the general observation is that ophiolites in the central Philippines were generated with variable degrees of subduction influences (e.g., Faustino et al 2006;Dimalanta et al 2009;Yumul et al 2013).…”
Section: Implications For Tectonic Settingsmentioning
confidence: 99%